1997
DOI: 10.1136/bmj.314.7080.569
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of weight bearing exercise in older women in relation to bone density and falls

Abstract: Objective: To investigate the effect of socioeconomic group (with reference to age and sex) on the rate of, course of, and survival after coronary events. Design: Community coronary event register from 1985 to 1991. Setting: City of Glasgow north of the River Clyde, population 196 000. Subjects: 3991 men and 1551 women aged 25-64 years on the Glasgow MONICA coronary event register with definite or fatal possible or unclassifiable events according to the criteria of the World Health Organisation's MONICA projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 4 publications
1
49
0
5
Order By: Relevance
“…Anyway, our results, taking into account the duration and the intensity of the program load on the spine and femur, should not be considered discordant from those reported by others. (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) More surprising is the lack of effects on bone mass and density of the ultradistal radius, measured by both traditional DXA and pQCT. From this point of view, our study cannot be easily compared with others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anyway, our results, taking into account the duration and the intensity of the program load on the spine and femur, should not be considered discordant from those reported by others. (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) More surprising is the lack of effects on bone mass and density of the ultradistal radius, measured by both traditional DXA and pQCT. From this point of view, our study cannot be easily compared with others.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, no beneficial effects were observed (5)(6)(7)(8) in others the increase in bone mineral density (BMD) were very limited. (9)(10)(11)(12)(13) The most striking and consistent increases in bone mass in postmenopausal women are observed after prolonged high intensity training (14)(15)(16)(17)(18) and in those on hormone replacement therapy (HRT). (11) The discrepancy in the range of BMD changes are likely due the heterogeneity of the exercise program and of the method of evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…When this exercise program was tested in a sample of community-dwelling men and women over the age of 65, the adjusted analysis was not significant, however the point estimate (relative hazard = 0.87) may be clinically important [84]. The Cochrane meta-analysis of four studies [60][61][62][63] (three community and one nursing home) concluded that untargeted exercise alone had no evidence of effectiveness. A later study [94] found that a 12-week program of exercises (strength, endurance, mobility and balance) in the community did not prevent falls at 12 weeks in older men (mean age 75 years) with at least one fall risk factor.…”
mentioning
confidence: 99%
“…Mortalität (van Haastregt, Diederiks, van Rossum, de Witte, Voorhoeve, & Crebolder, 2000;van Rossum, Frederiks, Philipsen, Portengen, Wiskerke, & Knipschild, 1993;Carpenter & Demopoulos, 1990), Muskelkraft (Woo, Hong, Lau, & Lynn, 2007;Lord, Ward, Williams, & Strudwick, 1995), Koordinationsfähigkeit (Woo et al, 2007;Lord et al, 1995), Reaktionszeit (Lord et al, 1995), Gehgeschwindigkeit (Steadman, Donaldson, & Kalra, 2003;Liu-Ambrose, Khan, Eng, Lord, & McKay, 2004;Woo et al, 2007), posturale Balance (Swanenburg, De Bruin, Stauffacher, Mulder, & Uebelhart, 2007), StandSitz-Performance (Lord et al, 2005), Knochendichte (Harwood, Sahota, Gaynor, Masud, & Hosking, 2004;Greenspan, Resnick, & Parker, 2003;Swanenburg et al, 2007) und allgemeiner Gesundheitsstatus (McMurdo, Mole, & Paterson, 1997;Carter et al, 2002;Barnett, Smith, Lord, Williams, & Baumand, 2003). Jedoch berücksichtigt die Begrenzung der Endpunkte auf klinische Parameter die Präferenzen der Zielgruppe nicht ausreichend (Langer et al, 2012;Nilsen, Myrhaug, Johansen, Oliver & Oxman, 2006;PCORI, 2012).…”
Section: Klientenzentrierte Endpunkteunclassified
“…Zu den bedeutenden klientenzentrierten Endpunkten zählen z.B. die Anzahl an Stürzen (McMurdo et al, 1997;Harwood et al, 2005;Lord et al, 2005;Porthouse et al, 2005;Swanenburg et al, 2007), die Anzahl an Gestürzten (McMurdo et al, 1997;Harwood et al, 2005;Porthouse et al, 2005), die Sturzangst (Porthouse et al, 2005;Lannin, Clemson, McCluskey, Lin, Cameron, & Barras, 2007;Lin, Wolf, Hwang, Gong, & Chen, 2007) sowie die Lebensqualität (Gallagher & Brunt, 1996;Harwood, Foss, Osborn, Gregson, Zaman, & Masud, 2005;Lannin et al, 2007) und Mobilität (Lannin et al, 2007). Da die individuelle Partizipation und Teilhabe von Klienten/-innen am Leben in der Gesellschaft Handlungsmaxime und fester Bestandteil der Sozialgesetzgebung (SGB IX) sind, sind Endpunkte, die soziale Partizipation und Wertvorstellungen abbilden, stärker in den Fokus zu rücken (BAR, 2008;Welti, & Fuchs, 2007).…”
Section: Klientenzentrierte Endpunkteunclassified